The Board of Directors, Firm Size, Capital Structure, Financial Performance During the Covid-19 Crisis: Evidence from Indonesia - Noliviasari, Chintya; Siswantoro , Ely (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
This study investigates the impact of the board of directors, and firm size on financial performance with capital structure as intervening variable in manufacturing companies listed on the Indonesia Stock Exchange during the Covid-19 pandemic specifically in the period 2020-2021. The sample in this study was 114 companies determined by using purposive sampling. The board of directors in this study was measured using the number of the board of directors, company size using Ln Total Assets, capital structure using DER, and financial performance using ROA. We find that the board of directors has no effect on financial performance and capital structure, company size has a positif significant influence to financial performence and capital structure, and capital structure has a negative significant influence to financial performence. In addition, capital stucture is able to mediate the relationship of firm size on financial peformance, but fails to mediate the relationship of the board of directors on financial peformance